2021
DOI: 10.1371/journal.pcbi.1009213
|View full text |Cite
|
Sign up to set email alerts
|

An association between prediction errors and risk-seeking: Theory and behavioral evidence

Abstract: Reward prediction errors (RPEs) and risk preferences have two things in common: both can shape decision making behavior, and both are commonly associated with dopamine. RPEs drive value learning and are thought to be represented in the phasic release of striatal dopamine. Risk preferences bias choices towards or away from uncertainty; they can be manipulated with drugs that target the dopaminergic system. Based on the common neural substrate, we hypothesize that RPEs and risk preferences are linked on the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…We hypothesise that levodopa increases risk-taking behaviour via overstimulation at both D1 and D2 receptor level, while a single low dose of haloperidol, as previously reported (Frank and O'Reilly 2006), may block D2 receptors pre-and post-synaptically and may paradoxically lead to higher striatal dopamine acting on remaining striatal D1 receptors, causing speedier decision without influencing risk tolerance. These effects could also fit with a recently proposed computational model of the basal ganglia (Moeller and Bogacz 2019;Moeller et al 2021). Furthermore, our data suggest that the actual dopaminergic drug effect may be dependent on the individual's baseline dopamine state, which may influence our therapeutic decision as clinicians in the future.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…We hypothesise that levodopa increases risk-taking behaviour via overstimulation at both D1 and D2 receptor level, while a single low dose of haloperidol, as previously reported (Frank and O'Reilly 2006), may block D2 receptors pre-and post-synaptically and may paradoxically lead to higher striatal dopamine acting on remaining striatal D1 receptors, causing speedier decision without influencing risk tolerance. These effects could also fit with a recently proposed computational model of the basal ganglia (Moeller and Bogacz 2019;Moeller et al 2021). Furthermore, our data suggest that the actual dopaminergic drug effect may be dependent on the individual's baseline dopamine state, which may influence our therapeutic decision as clinicians in the future.…”
mentioning
confidence: 53%
“…For example, pathological gambling is an impulse control disorder that involves increased risk-taking and is linked to hyperdopaminergic states (Pine et al 2010;Sinha et al 2013;Voon et al 2010;du Hoffmann and Nicola 2014). In line with this, it has been proposed that dopamine controls the effect of risk on choice (Moeller et al 2021). According to this theory, increasing dopamine levels should lead to risky decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eqs 5 and 6 , G and N denote the synaptic inputs in the direct and indirect pathway respectively [ 22 ], and λ is a coefficient determining the accuracy with which the standard deviation can be encoded (as explained below). Term –1 in Eq 6 in necessary for the neural implementation of scaled prediction error computation (as will be seen later).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been recently demonstrated that even a brief, burst–like activation of dopaminergic neurons changes the activity levels of striatal neurons [ 39 ]. Additionally, it has been shown that reward prediction errors modulate the tendency to make risky choices [ 22 ], and risk attitudes are known to depend on the balance between the activities in direct and indirect pathways [ 40 , 41 ]. In this paper, we demonstrated that a more realistic assumption, that the dopamine signal encoding prediction error also changes the activity levels in striatum, enables scaling of prediction errors by uncertainty.…”
Section: Discussionmentioning
confidence: 99%